What is the Way Allah's Word Manifests Itself in Yemeni Arabic? - Yousef Ali Ahmed Saleh Al-Nahdi; Yenni Patriani; Zhao Shuo; Fuzhen Si (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: What is the Way Allah's Word Manifests Itself in Yemeni Arabic?In this paper, the author shows how ‘Allah’ is used in daily Yemeni Arabic conversations. The term Allah has a variety of meanings in Yemeni Arabic, as it does in the Arab world, reflecting the belief that Allah alone is in charge of all the affairs, grants blessings, and either encourages or criticizes someone to do something. The result of this is that the term Allah appears in several expressions when the term is part of a sentence containing the word. For example, there are expressions that have over one meaning, such as Allah alaik, which signifies two literal meanings. The word Allah can also be found in other expressions, but with entirely different meanings, including moaning or aiming for guidance. I conducted a study looking at the occurrences of social life contact, reactions, and the cultural influence of native Yemenis. The rest of this paper explores some of the other most common expressions used in Yemeni society, which shows the word is heavily influenced by religion and culture in its use in Yemeni society.Abstract: Bagaimana Firman Allah Mewujudkan Dirinya dalam Bahasa Arab Yaman?Dalam makalah ini, penulis menunjukkan bagaimana 'Allah' digunakan dalam percakapan bahasa Arab Yaman sehari-hari. Istilah Allah memiliki berbagai arti dalam bahasa Arab Yaman, seperti halnya di dunia Arab, yang mencerminkan keyakinan bahwa hanya Allah yang mengatur semua urusan, memberikan berkah, dan mendorong atau mengkritik seseorang untuk melakukan sesuatu. Akibatnya, istilah Allah muncul dalam beberapa ekspresi ketika istilah tersebut merupakan bagian dari kalimat yang mengandung kata tersebut. Misalnya, ada ungkapan yang memiliki lebih dari satu arti, seperti Allah alaik, yang menandakan dua arti literal. Kata Allah juga dapat ditemukan dalam ungkapan lain, tetapi dengan arti yang sama sekali berbeda, termasuk mengerang atau membidik petunjuk. Saya melakukan penelitian dengan melihat kejadian kontak kehidupan sosial, reaksi, dan pengaruh budaya penduduk asli Yaman. Sisa dari makalah ini mengeksplorasi beberapa ekspresi paling umum lainnya yang digunakan dalam masyarakat Yaman, yang menunjukkan kata tersebut sangat dipengaruhi oleh agama dan budaya dalam penggunaannya di masyarakat Yaman..